Catestatin prevents endothelial inflammation and promotes thrombus resolution in acute pulmonary embolism in mice. Issue 11 (22nd November 2019) - Chen, Hua; Liu, Dongxia; Ge, Lan; Wang, Tao; Ma, Zhenzhen; Han, Yuping; Duan, Yawei; Xu, Xin; Liu, Wei; Yuan, Jing; Liu, Jing; Li, Ruyi; et al.
Abstract: Catestatin (CTS), a catecholamine-release inhibitory peptide, exerts pleiotropic cardiac protective effects. Pulmonary embolism caused by deep vein thrombosis involving vascular dysfunction. The present study aims to investigate the effects of CTS on thrombus formation that may inhibit the development of pulmonary embolism and its potential pathway. Acute pulmonary embolism (APE) model was developed as an in vivo model. The effects of CTS on mice with APE were examined. Human pulmonary artery endothelial cells (HPAECs) were pretreated with CTS before thrombin stimulation, and endothelial inflammation and underlying mechanisms were evaluated in vitro . That plasma CTS level was decreased in APE mice, while the number of platelets was significantly increased. The decreased circulating CTS level negatively associated with the number of platelets. CTS administration increased the survival rate of APE mice and protected against microvascular thrombosis in lung. APE-induced the increase in platelets number and plasma von Willebrand factor (VWF) were inhibited by CTS. Platelets from CTS-treated APE mice showed impaired agonist-induced platelets aggregation and spreading. CTS also ameliorated APE-induced the systemic inflammatory response. In in vivo study, thrombin-induced the increase in inflammation, TLR-4 expression and p38 phosphorylation were abrogated by CTS in HPAECs. Furthermore, TLR-4 overexpression inhibited the effect of CTS on VWF release and inflammation in HPAECs. Collectively, CTS increases thrombus resolution by attenuating endothelial inflammation at partially via inhibiting TLR-4-p38 pathway. The present study may provide a novel approach for anti-thrombosis.